Is medical training solely to blame? Generational influences on the mental health of our medical trainees - Shireen Suliman; Margaret Allen; Tawanda Chivese; Angelique E. de Rijk; Richard Koopmans; Karen D. Könings (Medical Education Online)
Introduction The negative impact of medical training on trainee mental health continues to be a concern. Situated within a sociocultural milieu, Generation Z and Generation Y, defined by their highly involved parents and the widespread use of technology, currently dominate undergraduate and graduate medical education respectively. It is necessary to explore medical trainees’ generational characteristics and job-related factors related to stress, burnout, depression, and resilience. This might provide different perspectives and potential solutions to medical trainees’ mental health.Methods A cross-sectional study was conducted among medical trainees (students and residents) from two institutions in Qatar. A self-administered online survey included measures for trainees’ social media overuse, their parent’s parenting style, the educational support by the clinical teacher, job (demands, control, and support), and work-life balance and their relation with their stress, burnout, depression, and resilience. Relationships were tested with multiple linear regression analyses.Results Of the 326 medical trainees who responded, 142 (44%) trainees − 93 students and 49 residents – completed all items and were included in the analysis. Social media overuse and inability to maintain a work-life balance were associated with higher levels of stress, depression, and student burnout. Higher levels of job support were associated with lower levels of stress, depression, and resident burnout, and a higher level of resilience. Job control was associated with lower burnout levels. Parenting style was unrelated to trainees’ mental health.Discussion The two generations ‘Y’ and ‘Z’ dominating current medical training showed more stress-related complaints when there is evidence of social media overuse and failure to maintain a work-life balance, while job support counterbalances this, whereas parenting style showed no effect. Measures to enhance medical trainees’ mental health may include education about the wise use of social media, encouraging spending more quality social time, and enhancing job support and job control.